The influence of limited financial resources on daily travel practices. A case study of low-income households with children in the Hanover Region (Germany) - Rozynek, Caroline; Schwerdtfeger, Stefanie; Lanzendorf, Martin (Journal of transport geography, 2022)
Being mobile is essential to participate in social life. However, as transport involves costs, this is a particular challenge for people on low incomes. Households with children are, especially, at an increased risk of poverty. To provide a deeper understanding of how financial poverty affects the daily travel practices of low-income families and how they cope with their limited financial resources, we conducted 16 qualitative problem-centred interviews with low-income families in Ronnenberg (Hanover Region, Germany). Although all the interviewees have to cope with limited financial resources, their daily travel practices differ. We identify four types of daily travel practices for these families: (1) car-centred, (2) car-reduced, (3) public transport oriented and (4) non-motorised. For a more detailed analysis on how poverty affects transport and participation, we use the practice theory perspective (Shove et al., 2012). Our analysis highlights that the car plays a significant role despite poverty for some families. However, other low-income families manage their daily life with public transport and non-motorised modes only. Our results show that low-income households with children have several strategies for organising and financing their daily travel practices. One strategy is direct and indirect support for travel from their social network. Furthermore, some families forgo leisure activities with entrance fees or higher travel costs. •Typology of low-income families by their daily travel practices.•The competence to finance, organise or borrow materials needed for travel enhance low-income families' mobility options.•Low-income families' social networks can compensate transport disadvantages through direct and indirect financial support.•Low-income families experience transport-related social exclusion.